THE PROBLEM OF MULTICULTURALISM: Radicalism Mainstreaming through Religious Preaching in Surakarta (State Islamic University (UIN) of Sunan Ampel Surabaya, 2010)
This study aims at identifying the material scope of religious preaching and sermon; and describing the multicultural aspects conveyed in the religious preaching and sermon. As the subject of analysis, it focuses on religious sermons delivered by preachers in Surakarta, Central Java, Indonesia. Using content and discourse analysis, this study finds that: the diversity of the society gains little attention by different religious preachers; instead of multicultural values, the religious preaches and sermons contain some anti-multicultural values, such as self-righteousness, prejudices and stereotypes of other groups; the subject of religious preaches and sermons implied the intensity of the purification movement; and the development of Islam implies the tendency of religious radicalism as reflected in the hostility towards the local culture, foreign people, and non-Muslims.